2014
DOI: 10.1016/j.carbpol.2014.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of starch-based films plasticised by glycerol and by the ionic liquid 1-ethyl-3-methylimidazolium acetate: A comparative study

Abstract: This paper reports the plasticisation effect of the ionic liquid, 1-ethyl-3-methylimidazolium acetate ([Emim][OAc]), as compared with the traditionally used plasticiser, glycerol, on the characteristics of starch-based films. For minimising the additional effect of processing, a simple compression moulding process (which involves minimal shear) was used for preparation of starch-based films. The results show that [Emim][OAc] was favourable for plasticisation, i.e., disruption of starch granules (by scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 42 publications
14
67
1
Order By: Relevance
“…Thus, starch has attracted a great deal of interest as a potential alternative to conventional plastics for packaging applications. Several studies have investigated the development and characterization of starch based films from corn [4,[6][7][8], potato [9][10][11][12][13], cassava [14][15][16][17][18][19][20], banana [21], yam [22,23], pea [1], sago [24][25][26], rice [27][28][29][30], maize [31][32][33][34], Kudzu [35] and agar [36][37][38][39]. According to Sahari et al [40] sugar palm starch is also a potential biopolymer material for making biodegradable films.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, starch has attracted a great deal of interest as a potential alternative to conventional plastics for packaging applications. Several studies have investigated the development and characterization of starch based films from corn [4,[6][7][8], potato [9][10][11][12][13], cassava [14][15][16][17][18][19][20], banana [21], yam [22,23], pea [1], sago [24][25][26], rice [27][28][29][30], maize [31][32][33][34], Kudzu [35] and agar [36][37][38][39]. According to Sahari et al [40] sugar palm starch is also a potential biopolymer material for making biodegradable films.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported in this article that the maximum conductance that TPS plasticized by [Amim]Cl can achieve is 10 -1.6 S cm -1 at 14.5 wt% water content, which means IL can also broaden the application of TPS film. TPS processed by extruders utilising IL as plasticiser has been reported in another study (Sankri et al, 2010 (Xie et al, 2014). This showed that the combined plasticisers contribute to a significant reduction in granule remnants compared with glycerol, resulting in highly amorphous structure.…”
Section: Ionic Liquids As Plasticisersmentioning
confidence: 73%
“…Other strong peaks at 2θ of 7°, 13°, 20° and 22°, which overlaps with 23°, are indicative of a V-type crystalline structure (Xie et al, 2014). The diffractogram of RMS-E9-RH75 shows a similar pattern, however with lower intensity.…”
Section: Xrdmentioning
confidence: 89%
See 2 more Smart Citations